2023
DOI: 10.3390/molecules28186640
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modelling and Optimization for Facile Synthesis of Structured Activated Carbon (ACs) from Adansonia kilima (Baobab) Wood Chips Integrating Microwave-Assisted Pyrolysis for the Elimination of Lead (II) Cations from Wastewater Effluents

Santhana Sellamuthu,
Zaira Chowdhury,
Khalisanni Khalid
et al.

Abstract: In this research, activated carbon (AC) was synthesized from ligno-cellulosic residues of Adansonia kilima (Baobab) wood chips (AKTW) using two-step semi-carbonization and subsequent pyrolysis using microwave-induced heating (MWP) in the presence of a mild activating agent of K2CO3. The influence of process input variables of microwave power (x1), residence time (y1), and amount of K2CO3 (z1) were analysed to yield superior quality carbon having maximum removal efficiencies (R1) for lead (II) cations from wast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…For fixed carbon content percentages, β3; temperature (𝐴 1 ), time (𝐵 1 ), and ratio (𝐶 1 ) were significant model terms (Table 5). The obtained standard deviations (SD%) and coefficient of variation (CV) were minimal, implying that the suggested models are dependable (Tables 3, 4, and 5) (Sellamuthu et al 2023). The signal/noise ratio (s/n) achieved in this case exceeded 4, indicating sufficient precision for the proposed models (Sellamuthu et al 2023) The impact of processing variables on percentage removal (β1) According to the F values reported in Table 3, it was concluded that the pyrolysis temperature (𝐴 1 ) had the strongest influence on percentage removal (β1), and the duration (𝐵 1 ) and ratio (𝐶 1 ) had approximately lower effects on this response.…”
Section: Fitting Of Regression Model and Statistical Analysis For Act...mentioning
confidence: 99%
See 4 more Smart Citations
“…For fixed carbon content percentages, β3; temperature (𝐴 1 ), time (𝐵 1 ), and ratio (𝐶 1 ) were significant model terms (Table 5). The obtained standard deviations (SD%) and coefficient of variation (CV) were minimal, implying that the suggested models are dependable (Tables 3, 4, and 5) (Sellamuthu et al 2023). The signal/noise ratio (s/n) achieved in this case exceeded 4, indicating sufficient precision for the proposed models (Sellamuthu et al 2023) The impact of processing variables on percentage removal (β1) According to the F values reported in Table 3, it was concluded that the pyrolysis temperature (𝐴 1 ) had the strongest influence on percentage removal (β1), and the duration (𝐵 1 ) and ratio (𝐶 1 ) had approximately lower effects on this response.…”
Section: Fitting Of Regression Model and Statistical Analysis For Act...mentioning
confidence: 99%
“…The obtained standard deviations (SD%) and coefficient of variation (CV) were minimal, implying that the suggested models are dependable (Tables 3, 4, and 5) (Sellamuthu et al 2023). The signal/noise ratio (s/n) achieved in this case exceeded 4, indicating sufficient precision for the proposed models (Sellamuthu et al 2023) The impact of processing variables on percentage removal (β1) According to the F values reported in Table 3, it was concluded that the pyrolysis temperature (𝐴 1 ) had the strongest influence on percentage removal (β1), and the duration (𝐵 1 ) and ratio (𝐶 1 ) had approximately lower effects on this response. When the ratio was adjusted at center/zero, the trend for sorption capacity was quantified and the combined impact of temperature (𝐴 1 ) and time (𝐵 1 ) was illustrated by 3D RSM mesh plot of Fig.…”
Section: Fitting Of Regression Model and Statistical Analysis For Act...mentioning
confidence: 99%
See 3 more Smart Citations